The Frequency Transducer of Magnetic Induction - Osadchuk, V. S.; Osadchuk А. V.; Chabanenko, V. V. (Elektronika ir Elektrotechnika, 2007)
Research the transducer of magnetic induction with a frequency output signal is represented on the basis of usage of reactive properties of transistor structures with negative resistance in the field of temperatures 77 K and 293 K. The analytical dependences of function of transformation and equation of sensitivity are obtained. The theoretical and experimental research has shown, that the sensitivity of the transducer makes a 1,5-2,25 kHz/mT, and at temperature 77 K increases approximately 10 times. Ill. 5, bibl. 7 (in English; summaries in English, Russian and Lithuanian).